Manchuria : : Administration - Great Britain Embassy (Japan); Great Britain Foreign Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1935)
Foreign Office file containing correspondence and memoranda relating to Japanese administration of Manchuria